STRESS LEVEL MANAGEMENT CAPACITY OF COLLEGE PRINCIPALS IN KERALA- EVALUATION THROUGH TEACHERS’ PERCEPTION (International Journal of Food and Nutritional Sciences, 2022)
In this article researcher made an attempt to study the stress level management capacity of college principals through the eyes of their respective teachers. Primary data were collected through surveys administered exclusively to college teachers, and Friedman test, Mann Whitney U test , Kruskal Wallis H test were employed to analyzed the collected data. The result of the study indicates that there is a significant difference in the operational activities of the principal, such as "can handle activities other than departments," "ability to raise funds from government and other activities," "conducting meetings on time," "emotional intelligence," and "overall operational ability," with respect to the types of organisations in which they are working. No difference was found on other variables.